Momentos que demarcam o percurso de formação de professores alfabetizadores: um olhar para o município de Nepomuceno-MG - Azarias, Lívia de Souza Tanus (2019)
The difficulties presented by teachers in the act of to literate have been the subject of debate in several fields of research, and as the problems in guaranteeing the mastery of reading and writing become evident, new public policies for training teachers are proposed as possibilities to understand, conceive, restructure and resignify the context of literacy. Therefore, the objective of this research was to analyze the moments that demarc ate the training course of literacy teachers demarcated in the teaching discourse, as well as to describe how much the courses of continuing education contribute to the practice pedagogical in relation to literacy, comparing how the knowledge acquired in experiences already tried and in the process of academic training are triggered in order to guarantee the performance and knowledge that the literacy teacher uses. The research adopted the qualitative approach, with emphasis on the description. As a methodological procedure for data collect, a semi -structured interview script recorded in audio was used, which was subsequently transcribed in full. The research subjects were six literate teachers of basic education of State and municipal schools, selected for participating in the National Pact Training Program for Literacy in The Right Age (NPLRA) (in Portuguese: PNAIC), in the municipality of Nepomuceno -MG. The data were analyzed by means of the content analysis technique, using the thematic analysis of Bardin (2009) and Minayo (2007), in which a categorization was made by means of the themes raised in the interviews. From the analysis of the speeches of the teachers were listed five (5) categories, each covering a certain subject about the knowledge acquired i n the process of academic education and literacy practices. It was found that the courses of continuing education, as well as the daily knowledge and practices add much to the performance of the literacy teachers because there is an exchange of experiences among the most experienced and the newly graduated. The speeches point to gaps in the initial formation, which did not allow the preparation to work in the literacy rooms, and most did not demonstrate a focus on literacy and became distant from true practice.